2006
DOI: 10.1088/0957-0233/17/6/030
|View full text |Cite
|
Sign up to set email alerts
|

On-line measurement of surface roughness by laser light scattering

Abstract: On-line roughness measurement of a surface with one-dimensional manufacturing marks is difficult to implement. For example, a contact stylus-type inspection method often does not perform very well or fails without any prior knowledge of the mark distribution on the surface. In this paper, we propose an on-line surface roughness measurement method based on laser light scattering, which is very effective for roughness measurement of one-dimensional manufacturing surfaces. The surface roughness is obtained from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 22 publications
0
30
0
Order By: Relevance
“…In this part, we explain the prototype of surface roughness [15,17,18,19,20] study using a group of arrays of antennas and single transmitter of wave towards the plate with normal incidence, before discussing the implementation of high resolution angle of arrival techniques [1,2], let us describe the type of surface's irregularities we are focused on.…”
Section: Proposed Prototype For On Dimensional Roughness Characterizamentioning
confidence: 99%
See 2 more Smart Citations
“…In this part, we explain the prototype of surface roughness [15,17,18,19,20] study using a group of arrays of antennas and single transmitter of wave towards the plate with normal incidence, before discussing the implementation of high resolution angle of arrival techniques [1,2], let us describe the type of surface's irregularities we are focused on.…”
Section: Proposed Prototype For On Dimensional Roughness Characterizamentioning
confidence: 99%
“…The roughness of surface is considered as random fluctuations [15,19] of protuberances that compose the material type of the surface, thus the roughness is random, and it can be described by two dimensional [19,20] or one dimensional function [17,18], we focus here on the last category, the statistical description of the randomness states that the height of The plate is placed in ( , ) xyplane, the lines of roughness are parallel to…”
Section: Proposed Prototype For On Dimensional Roughness Characterizamentioning
confidence: 99%
See 1 more Smart Citation
“…It was characterized by a low sensitivity to movements and vibrations of the measured elements. Lu and Tian used a similar approach [24]. This has been implemented in an optical measuring head of a similar design [23].…”
Section: Using Scattered Light For In-process Inspectionmentioning
confidence: 99%
“…Kamguem et al [5] demonstrated that roughness parameters (R a , R t and R z ) can be estimated by using only image-extracted features. Lu and Tian [6] used light scattering techniques to realize the online prediction of machined surface roughness. Two non-optical methods were also developed.…”
Section: Introductionmentioning
confidence: 99%